Tailored Charge Transfer Kinetics in Precursors for Organic Radical Batteries: A Joint Synthetic‐Theoretical Approach. Issue 2 (4th January 2023) - Zens, Clara; Friebe, Christian; Schubert, Ulrich S.; Richter, Martin; Kupfer, Stephan
Abstract: Invited for this month's cover is the group of Stephan Kupfer at the Friedrich Schiller University Jena. The image shows the charge transfer from TEMPO to thiophene in organic radical batteries. The Research Article itself is available at 10.1002/cssc.202201679 . Abstract : "Our research is focusing on alternatives namely organic batteries" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202201679 . View the Front Cover here: 10.1002/cssc.202202344 .